2019
DOI: 10.1039/c8se00614h
|View full text |Cite
|
Sign up to set email alerts
|

Catalysts for gasification: a review

Abstract: Gasification catalysts, either intrinsic to the feed or added, are discussed as to their advantages, disadvantages, and interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 419 publications
1
50
0
Order By: Relevance
“…As the temperature of gasification increases from 800 • C, the rate of Na released into the gas phase increases in a non-linear fashion. This is because Na released to the gas phase at lower temperatures is transferred to the produced char-forming channels in the carbon interface during gasification [24], often forming larger mesopores than other alkali metals. This makes sodium, much like potassium and calcium, an edge-recession catalyst [24,25].…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…As the temperature of gasification increases from 800 • C, the rate of Na released into the gas phase increases in a non-linear fashion. This is because Na released to the gas phase at lower temperatures is transferred to the produced char-forming channels in the carbon interface during gasification [24], often forming larger mesopores than other alkali metals. This makes sodium, much like potassium and calcium, an edge-recession catalyst [24,25].…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
“…This is because Na released to the gas phase at lower temperatures is transferred to the produced char-forming channels in the carbon interface during gasification [24], often forming larger mesopores than other alkali metals. This makes sodium, much like potassium and calcium, an edge-recession catalyst [24,25]. It has been shown that the presence of Na can effectively catalyze the water-gas shift reaction (CO + H 2 O → CO 2 + H 2 ), a mildly exothermic reaction, boosting the production of CO 2 and H 2 [24].…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these disposal practices jeopardize the land security and threaten the air safety (Wong et al 2018). Recognizing the aforementioned issues and considering the various disposal methods, the gasi cation technologies have attracted attentions due to their ability to convert carbonaceous waste to valuable products (Arnold and Hill 2019). However, the conventional gasi cation process has many drawbacks such as a demand for pure oxygen, external heat supplementation and high tar content than other methods.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these discarded waste activated carbons (WACs) are commonly disposed for landfills and via open burning treatment, which practices jeopardize the land security and threaten the air safety (Wong et al 2018). Recognizing the aforementioned issues and considering the various disposal methods, the chemical looping gasification (CLG) technologies have attracted attentions due to their ability to convert carbonaceous waste to valuable products (Arnold andHill 2019, Wang et al 2019). Typically, WAC has the advantages of high carbon content.…”
Section: Introductionmentioning
confidence: 99%